Correlation between the variation in observed melting temperatures and structural motifs of the global minima of gallium clusters: an ab initio study - Susan, Anju; Kibey, Aniruddha; Kaware, Vaibhav; Joshi, Kavita (Journal of Chemical Physics, 2013)
We have investigated the correlation between the variation in the melting temperature and the growth pattern of small positively charged gallium clusters. Significant shift in the melting temperatures was observed for a change of only few atoms in the size of the cluster. Clusters with size between 31-42 atoms melt between 500-600 K whereas those with 46-48 atoms melt around 800 K. Density functional theory based first principles simulations have been carried out on Ga-n(+) clusters with n = 31, ... , 48. At least 150 geometry optimizations have been performed towards the search for the global minima for each size resulting in about 3000 geometry optimizations. For gallium clusters in this size range, the emergence of spherical structures as the ground state leads to higher melting temperature. The well-separated core and surface shells in these clusters delay isomerization, which results in the enhanced stability of these clusters at elevated temperatures. The observed variation in the melting temperature of these clusters therefore has a structural origin. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4772470]

Rationalizing the role of structural motif and underlying electronic structure in the finite temperature behavior of atomic clusters - Susan, Anju; Joshi, Kavita (Journal of Chemical Physics, 2014)
Melting in finite size systems is an interesting but complex phenomenon. Many factors affect melting and owing to their interdependencies it is a challenging task to rationalize their roles in the phase transition. In this work, we demonstrate how structural motif of the ground state influences melting transition in small clusters. Here, we report a case with clusters of aluminum and gallium having same number of atoms, valence electrons, and similar structural motif of the ground state but drastically different melting temperatures. We have employed Born-Oppenheimer molecular dynamics to simulate the solid-like to liquid-like transition in these clusters. Our simulations have reproduced the experimental trends fairly well. Further, the detailed analysis of isomers has brought out the role of the ground state structure and underlying electronic structure in the finite temperature behavior of these clusters. For both clusters, isomers accessible before cluster melts have striking similarities and does have strong influence of the structural motif of the ground state. Further, the shape of the heat capacity curve is similar in both the cases but the transition is more spread over for Al-36 which is consistent with the observed isomerization pattern. Our simulations also suggest a way to characterize transition region on the basis of accessibility of the ground state at a specific temperature. (C) 2014 AIP Publishing LLC.

Multifaceted thermodynamics of Pb-n (n=16-24) clusters: a case study - Susan, Anju; Kaware, Vaibhav; Joshi, Kavita (Journal of Physical Chemistry C, 2015)
Thermodynamic response of small clusters is a challenging area of exploration, both experimentally and theoretically. In this article, we study the thermodynamic behavior of small Pb clusters (size 16-24) using Born-Oppenheimer molecular dynamics. A new ground state structure is reported for Pb-20. Except for Pb-21, all clusters fragment at temperatures above T-m[bulk] and show no signs of melting. Characteristic behavior like restricted diffusion and solid solid transition is discussed in detail. Variation in the isomerization temperature of these clusters is explained using the bond length analysis. Root mean square bond length fluctuations (delta(rms)) along with distribution of atoms about center of mass of the cluster as a function of time and distance-energy (DE) plots are used to bring out the essential features of Pb cluster thermodynamics. Analysis carried out using these parameters, and their interpretation regarding state of the system, are discussed in detail. We highlight that it is not possible to define ``liquid state'' for these small clusters, in the conventional frame of understanding.